EVALUATION THE LEVELS OF HOMOCYSTEINE AND FERRITIN IN CHRONIC KIDNEY DISEASE (CKD) WITH ANEMIA - Intesar Abdulwahed Shaker; Muhammet Donmez; Abdullah Adil Raoof (Academia Science Repository, 2023)
Aims: The current study was aimed to estimate the levels of homocysteine, and ferritin in chronic kidney disease (CKD). Materials and methods: In this study, 100 blood samples (100) were taken from chronic renal failure (CRF) patients ranging in age from 35 to 70 years. From April to May 2023, those patients visited Kirkuk General Hospital, and all were exposed to a personal interview utilizing a specially devised questionnaire format with entire history with full details. For patients and healthy subjects, 5ml was taken from each patient and healthy subjects (50) without any disease. Results: for kidney functions, urea and creatinine levels in patients significantly increased (P<0.05) than in control. Serum ferritin and homocysteine concentrations Patients' levels were significantly (P<0.05) higher than in control. Conclusions: It is concluded from the current study, and based on the results of the study, that there is a strong association between homocysteine levels and chronic renal failure, with changes in kidney function.